The essential guide to mold making and slip casting. - Martin, Andrew, ....- (New York : Lark crafts, 2006)
For potters, mold making is invaluable because it allows them to slip-cast identical multiples of their work-and this newly revised, now in color edition of Andrew Martin's classic is the definitive guide to the craft. No other volume has shown the processes in such how-to detail. It's overflowing with hundreds of photos, key techniques, projects, master artist profiles, and troubleshooting tips. A thorough introduction addresses materials and tools, and presents Martin's simple, unique template method for making clay prototypes. Create easy one-piece molds to make tiles, bowls, and platters, or multi-piece molds for more complex forms. An extensive overview covers slip formulation, while offering highly desired slip recipes for low-, mid-, and high-fire clay bodies. This will be the standard reference in every ceramist's library.
Keywords: Gietkunst